Significant of shipping performance in the term of letter of credit: the case of Agrifert Malaysia Sdn Bhd (AFM) / Safli Suriahani Mohd Isa - Mohd Isa, Suriahani (2011)
The significance of shipping performance in international trade in the context of the Letter of Credit can be look over the past two decades whereby exporting and importing has been one of the fastest growing economic activities. In Malaysia, we have an organization that handle all the export and import fertilizers of Palm oil towards Malaysia. Agrifert Malaysia Sdn Bhd is the international trade organization(AFM). AFM also assists in trade matching between foreign exporters and Malaysia importers. The need for further research work discussed in this report. In determining the significant factors which contribute to determining in shipping performance, some variables are taken to be used in order to measure the most influences factors towards shipping performances in the term of letter of credit in their product to the world which might influences the establishment of AFM as one of the organization who responsible and number One company who can produce a 1million of Ton Raw material product of fertilizers in Malaysia in the international market. The selected variables include documentation, expiration and amount and revocation. The objective of the study is to evaluate whether the documentation, expiration and amount and revocation has significant relationship towards shipping performance. Data collected through questionnaire from the respondents under shipping and finance department who directly involved in Letter of Credit activities towards Oversea exporters. There are documentation activity, expiration and amount and revocation. By using the Statistical Program Social Science (SPSS), the results from this research show that documentation activity and expiration and amount have moderate relationship towards shipping performance and revocation have strong relationship towards shipping performance of AFM.